2D O‘LCHAMLI P-N-O‘TISHNING O‘TA YUQORI CHASTOTALI MAYDON TA’SIRIDA O‘ZGARISHI - Kosimova, M.O.; Maxmudov, A.S. (SCIENCE and SOCIETY, 2025)
It was studied how the single-layer quantum density of MoS2 changes according to the Fermi level under the action of a microwave field. It was shown that in 2D materials, a higher quantum density value serves to increase the operating speed and sensitivity of transistors, and the oxide density increases the durability of the material under an electric field.